Soil Geochemistry of Loess Landscapes, Shawnee Hills, Southern Illinois, United States. Issue 4 (4th June 2013) - Wilson, M. A.; Indorante, S. J.; Lee, B. D.; Follmer, L. R.; Williams, D. R.; Fitch, B. C.; McCauley, W. M.; Bathgate, J. D.; Kabrick, J. M.
Abstract : A study was initiated in soils of two southern Illinois loess‐derived landscapes to investigate the distribution of selected trace and major elements. The objective of the research was to link the distribution of elements in different landscape positions to important soil and landscape processes. Seventeen pedons (representing different geomorphic hillslope positions) at the Morgan Pond (MP) and Bean Ridge (BR) sites were sampled by horizon. Data were evaluated by grouping selected horizons (A, Bt) by site (MP and BR) as well as by geomorphic hillslope position. Results show that relative concentrations of total As, Cr, Cu, V, Ni, Pb, Se, and Zn between these two sites were impacted by differences in inherent particle size distribution of the parent material. These elements were also greater in Bt versus A horizons within each site, suggesting that select elements were redistributed by clay illuviation processes. Barium, Ca, Cd, Hg, and Pb were all significantly elevated in A relative to Bt horizons at the BR site and were strongly correlated with total C, suggesting biocycling and trace element bioaccumulation were important in landscape positions of this site. The MP site lacked this same concentration of elements in surface horizons, demonstrating the effect of accelerated erosion due to more intensive cropping history. When grouping data by landscape position, elemental distribution and Bt/A clay ratios showed that landscape stability was greatest in summit positions relative to other positions (summit > shoulder > backslope positions), confirming that relative amount of soil erosion was also related to landscape position among these sites.